Первые признаки процессов карбонового углеобразования в Львовско-Волынском бассейне - Шульга, В.; Костик, И.; Матрофайло, М.; Король, Н. (Інститут геологічних наук НАН України, 2008)
Conditions of the beginning of Carboniferous coal-formation (Late Tournaisian – the beginning of Late Visean) in Lviv-Volyn basin are reconstructed. First signs of coal-formation processes are established in Late Tournaisian deposits. Process of origination of coal-bearing formation proceeded gradually and were characterised by unfavourable conditions. Appearance of environments favourable for to extension paleo-peat-bogs refers to Early Visean. Late Tournaisian deposits of Khoriv suite correspond to "germinal" period of development of coal-bearing formation of Lvіv-Volyn basin, that is why its lower boundary is held in the base of the mentioned suite. Воссозданы условия начала карбонового углеобразования (поздний турне – начало позднего визе) в Львовско-Волынском бассейне. Первые признаки процессов углеобразования установлены в отложениях позднего турне. Процесс зарождения угленосной формации протекал постепенно и характеризовался неблагоприятными условиями. Появление обстановок, благоприятствующих распространению палеоторфяников, относится к раннему визе. Позднетурнейские отложения хоревской свиты соответствуют «зародышевому» периоду развития угленосной формации Львовско-Волынского бассейна, в связи с чем ее нижняя граница проводится по основанию указанной свиты.